1995
DOI: 10.1016/s0006-3495(95)80193-1
|View full text |Cite
|
Sign up to set email alerts
|

Metal-ligand complexes as a new class of long-lived fluorophores for protein hydrodynamics

Abstract: We describe the use of asymmetric Ru-ligand complexes as a new class of luminescent probes that can be used to measure rotational motions of proteins. These complexes are known to display luminescent lifetimes ranging from 10 to 4000 ns. In this report, we show that the asymmetric complex Ru(bpy)2(dcbpy) (PF6)2 displays a high anisotropy value when excited in the long wavelength absorption band. For covalent linkage to proteins, we synthesized the N-hydroxy succinimide ester of this metal-ligand complex. To il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(139 citation statements)
references
References 37 publications
(39 reference statements)
9
127
0
3
Order By: Relevance
“…This property provides information about rotational motions from the steady-state or time-resolved anisotropies. We found that the ruthenium complexes display polarized emission, allowing their use as anisotropy probes [63][64][65][66][67]. For these complexes the emission is from a metal-ligand charge transfer (MLCT) state.…”
Section: Microsecond Biopolymer Dynamicsmentioning
confidence: 97%
“…This property provides information about rotational motions from the steady-state or time-resolved anisotropies. We found that the ruthenium complexes display polarized emission, allowing their use as anisotropy probes [63][64][65][66][67]. For these complexes the emission is from a metal-ligand charge transfer (MLCT) state.…”
Section: Microsecond Biopolymer Dynamicsmentioning
confidence: 97%
“…The long lifetime increases the sensitivity by giving the probe more time to interact with the environment, and it allows the short-lived autofluorescence from the sample to be discarded. Phosphorescence anisotropy measurements can also be used to study the rotational diffusion of large proteins, whose movement is too slow to be measured with fast fluorescence decays [182,183]. Besides life sciences, PLIM has been used to study air-flow and pressure in aerodynamic studies [184], and for temperature measurements in industrial thermometry applications [185].…”
Section: Long Lifetime Measurementsmentioning
confidence: 99%
“…[38,39] The as-prepared [Ru-A C H T U N G T R E N N U N G (bpy) 2 Cl 2 ] (0.16 g), NaHCO 3 A C H T U N G T R E N N U N G (0.16 g), and 2,2'-bipyridine-4,4'-dicarboxylic acid (0.12 g) were added to a solution of methanol and H 2 O solution (20 mL; 4:1 v/v) and the stirred solution was heated for 4 h. The solution was cooled in an ice bath for 7 h, and the pH of the solution was adjusted with hydrochloric acid to pH 4.4. The formed precipitate was filtered and washed with methanol.…”
Section: Fabrication Of the Mb-au-cds Biocomplexmentioning
confidence: 99%